ACTIVITIES RESULTS AIMED AT IMPROVED MEDICAL ASSISTANCE TO THE VASCULAR PATIENTS IN TOMSK REGION - D. M. Plotnikov (Bûlleten' Sibirskoj Mediciny, 2013)
Acute disorders of cerebral circulation remain serious medical and social problem associated with high disability and mortality rates. Since 2011 Tomsk oblast is a participating member of the medical campaign aimed at improved medical services to the vascular patients. The preliminary implementation data analysis for 2012 revealed improvement of most of the indices of medical support to patients suffering from acute cerebral circulation; increased number of the in-patient cases (Regional Vascular Center and primary vascular department), decreased lethality rates from strokes, specifically hemorrhagic cases. Strict observance of the Regulations on Medical Assistance for stroke patients and the using of modern methods of therapy allowed to decrease hospital mortality in the Primary Vascular Departments and early mortality in the Regional Vascular Center. The active implementation of neurorehabilitation approaches resulted in the increased number of patients who do not require third parties’ assistance. Analysis of the work of the departments helped to identifying current problems and perspectives of further development of special medical care for stroke patients.